A facile microwave assisted one pot synthesis of novel xanthene derivatives as potential anti-inflammatory and analgesic agents - Banerjee, Anupam G.; Kothapalli, Lata P.; Sharma, Piyoosh A.; and et al (Elsevier B.V., 2011)
Microwave assisted irradiation of resorcinol and substituted aryl aldehydes using sulfamic acid as catalyst afforded novel 9-aryl-9H-xanthene-3,6-diol derivatives (1a–f) in good yields. The newly synthesized compounds which were previously selected on the basis of PASS prediction were tested for anti-inflammatory activity using carrageenan-induced rat paw edema and analgesic activity using acetic acid induced writhing and formalin-induced paw edema in mice along with the estimation of gastric ulcerogenicity index. Compounds 1e and 1f exhibited significant anti-inflammatory and analgesic activities as compared to standard drug. The study also revealed that compounds (1a–f) showed minimum or no ulcerogenicity in mice as that of the standard drug.
Keywords: Analgesic activity; Anti-inflammatory activity; Microwave reaction; PASS prediction; Sulfamic acid; Xanthene